IMPROVING "ETHNIC EPIC" PRODUCT COMPETITIVENESS THROUGH THE PKM PROGRAM IN FOSTERING STUDENT ENTREPRENEURIAL SPIRITS - Ninda Rachmawati (JOURNAL KOPERASI DAN MANAJEMEN, 2022)
Purpose – The economy is one factor in a country's progress. Each country is competing to boost the productivity of its economy. The Indonesian economy is ranked 17th in the world. Indonesia's economic growth is significant, and it cannot be separated from the role of small and medium-sized enterprises (SMEs) in supporting the growth of exports and imports. Tote bag manufacturers are one type of SME that can be seeded. Design/methodology/approach – Problems impeding the development and productivity of SME shoes, particularly in the Malang area, will be classified into four categories: (1) human, (2) process, (3) facilities, and (4) business competition. Use descriptive methods to improve product competitive in PKM program. Findings – According to this research, the most important issue affecting the development of SMEs in Malang is human resources. The Kaizen strategy (5S) will be used to solve these problems, along with the training student creativity program (PKM) and the P-Course concept. These enhancements will result in strategies to increase the overall productivity of SMEs by focusing on working and evaluating how the system works. This strategy is expected to address the weaknesses of existing SME shoes in order to prepare for the upcoming global competition. Research limitations/implications – This research only uses students in STIEKOP Malang, where they apply the proposal in the PKM program. If any SME in the Malang Area uses it, it will serve a great purpose. Originality/value – This instilled the entrepreneurial spirit in STIEKOP Malang students as they grew up. It must be supported with any element to create young entrepreneurs. Keywords: SME, Economic, PKM, Entrepreneur Paper type: Case Study